Effects of Concentration and Temperature of Nutrient Solution on Growth and Camptothecin Accumulation of Ophiorrhiza pumila - Lee, Ji-Yoon (Plants (Basel), 2020)
The medicinal plant, Ophiorrhiza pumila, naturally grows on the floors of humid inland forests in subtropical areas. It accumulates camptothecin (CPT), which is used as an anti-tumor agent, in all organs. We investigated the optimal hydroponic root-zone environments for growth and CPT accumulation in O. pumila in a plant factory. In experiment 1, to determine the appropriate nutrient solution concentration (NSC), O. pumila was cultivated using four concentrations (0.125, 0.25, 0.5, and 1.0 times) of a commercial solution for 63 days after the start of treatment (DAT). The electrical conductivity of these NSCs was 0.6, 0.9, 1.5, and 2.7 dS m(−1), respectively. The total dry weights at 0.25 and 0.5 NSCs were higher than those at the other two NSCs. CPT content at 0.25 NSC was significantly higher than those at other NSCs. In experiment 2, to investigate an appropriate nutrient solution temperature (NST), O. pumila was cultivated at four NSTs (10, 20, 26, and 35 °C, named as T10, T20, T26, and T36, respectively) for 35 DAT. The growth and CPT content at T20 was the highest among the treatments. Therefore, root-zone environments of 0.25 NSC and 20 °C of NST produced the best growth and CPT accumulation in O. pumila.